Syntheses and Properties of Conjugated Polymers Containing Thieno[2,3‐b]indole with Different Electron‐deficient Units - Kim, Juae; Chae, Sangmin; Gu, Dasom; Hong, Seungyeon; Lee, Sung Hun; Kim, Hyo Jung; Suh, Hongsuk (Bulletin of the Korean Chemical Society, 2019)
New conjugated polymers using electron‐rich unit, thieno[2,3‐b]indole (2‐TI), and various electron‐deficient units were synthesized for the utilization in the photovoltaics. The synthesized polymers (PTIBTI, PTITPD, and PTIID) with various types of electron‐deficient units showed different electronic structure and properties. The PTITPD provides the higher VOC through suitable energy level offset of LUMO (donor)‐LUMO (PC71BM) and improved JSC resulting from better crystallinity, charge carrier mobility and morphology, leading to the higher PCE value of OPV out of the series. This result illustrates that the combination of various electron‐deficient units affects the electronic structure, such as the HOMO/LUMO energy levels and bandgap in addition to the morphology and the carrier mobility, implying that variation of the electron‐deficient unit should be explored for the utilization of a given electron‐rich unit to produce the better performance of the device. Different electronic structure and properties of synthesized polymers with various types of electron‐deficient units.